Dietary supplement use among undergraduate male students in health and non-health cluster colleges of a public-sector university in Dammam, Saudi Arabia - Atta Abbas Naqvi; Rizwan Ahmad; Abdullah Abdul Wahid Elewi; Ayman Hussain AlAwa; Moayed Jafar Alasiri (BMC, 2018)
Abstract Background Dietary supplements (DS) are nutraceuticals that improve overall health and well-being of an individual as well as reduce the risk of diseases. Evidence indicates a rising prevalence of these products worldwide especially among college students. Studies have reported an increasing use of supplements among Saudi students. However, the scope of those researches was limited to prevalence data. Hence, the aim of our study was to document the prevalence, opinions, attitudes, reasons for use and monthly cost attributed to dietary supplement use. Methods A 3-month cross-sectional study was conducted to evaluate use of dietary supplement among health and non-health college students at a public-sector university in Dammam city, Saudi Arabia. It was conducted using Arabic version of the Dietary supplement questionnaire (DSQ-A). A total of 469 male students responded to the survey giving a response rate of 93.8%. The students were from ten colleges of the university. The data was analyzed by SPSS version 22. The study was approved by Institutional Review Board of Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia (IRB-UGS-2018-05-074). Results The overall prevalence of dietary supplement use in the university was 29.42%. In health cluster colleges, it was reported at 35.91% while in non-health cluster college it was 23.69%. Maintaining general health and well-being was the most common reason for use. Prevalence of multivitamins and whey proteins was approximately 23%. Average monthly cost of supplement was SAR 278.92 (USD 74.39). Cost was positively correlated (ρ = 0.305) with satisfaction score. Students preferred brand products (16.4%). 41.4% students opined that DS may prevent chronic illness if used regularly and agreed that they are good for health. Majority of students (65%) recommended DS use only upon physician's recommendation. College clusters and study-year was associated (p-value< 0.01) with students' opinion. Students in health cluster colleges were more likely to recommend supplements (OR 3.715, p-value< 0.0001). Conclusion Prevalence of dietary supplement use was lower than other local and international university students. Health cluster colleges had higher prevalence as compared to non-health cluster colleges. Multivitamins and whey protein were the most commonly used types of DS. Students preferred brand products, had positive opinions and attitudes towards dietary supplement. However, they recommended supplements use to others only upon a physician's recommendation.